The Influence of Government Expenditure and Public Purchasing Power On Poverty in Indonesia - Fauziana, Nanda; Mukhlis, Mukhlis; Rizkina, Azka (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study is motivated by the persistently high poverty rate in Indonesia despite the government’s implementation of various fiscal interventions and programs aimed at strengthening household purchasing power. Poverty remains a national strategic issue as it reflects social inequality and limited public access to basic needs. The objective of this research is to analyze the influence of government expenditure and household purchasing power on the poverty level in Indonesia over a long-term period. The study employs a quantitative approach using secondary time-series data obtained from the Central Statistics Agency, and the analysis is conducted using a multiple linear regression model to examine both partial and simultaneous effects among the variables. The findings indicate that, partially, government expenditure and household purchasing power do not have a significant effect on poverty, although both variables show a negative relationship that reflects a tendency toward poverty reduction. However, simultaneously, the two variables are found to have a significant influence on poverty levels, indicating that they jointly play an important role in explaining the dynamics of poverty in Indonesia. These results suggest that a combination of fiscal policy measures and efforts to strengthen household purchasing power remains essential for reducing poverty.